Nucleation increases the visual appeal of lager but does not alter overall likeability or drinking rate - David M. Troy; Olivia M. Maynard; Matthew Hickman; Marcus R. Munafò; Angela S. Attwood (BMC, 2022)
Abstract Background Glassware can be an effective vehicle to recruit customers, revive brands, build profits and increase alcohol consumption by capitalising on the immediacy of glassware to the point of consumption. The design of glassware can also contribute to harm reduction by slowing and reducing consumption. Nucleated bases have been added to lager glasses in recent years which allow carbon dioxide (CO2) to be more rapidly released and ascend through the solution. The aim of these studies was to investigate the effect of nucleated glasses on the likeability and drinking rate of lager in alcohol drinkers. Methods In Study 1, participants (n = 116) were asked to taste two glasses of lager (280 millilitres (ml) each) in separate 5-min taste tests and fill out a likeability questionnaire after each glass in a within-subjects design with one factor of glass (nucleated, non-nucleated). The primary outcome was the likeability of lager and the secondary outcome was volume consumption during taste tests. In Study 2, participants (n = 160) were asked to consume a pint of lager (568 ml) and fill out a likeability questionnaire in a between-subjects design with one factor of glass (nucleated, non-nucleated). The primary outcome was time taken to consume a pint of lager and secondary outcomes were the likeability of lager, mood and alcohol craving. Results There was no clear evidence that likeability of lager differed between nucleated and non-nucleated glasses in either study. In Study 1, a paired-samples t test found strong evidence that lager in nucleated glasses was more visually appealing (single item from likeability measure) than lager in non-nucleated glasses (mean difference (MD) = 10.2, 95% confidence interval (CI) 6.1, 14.2, p < 0.001). In Study 2, a linear regression found no clear evidence that lager was consumed at different rates from nucleated and non-nucleated glasses (nucleated: 16.9 min, non-nucleated: 16.3 min, MD: 0.6 min, 95% CI − 1.5, 2.7, p = 0.57). Conclusions Nucleated lager glasses do not appear to alter the likeability or consumption (volume consumed in Study 1 or drinking rate in Study 2) of lager, although they do seem to increase the visual appeal and refreshment of lager. This may increase the number of drinking episodes by making the drinking experience more enjoyable which may lead to increased alcohol related harm.